Depression in older adults from the municipality of Mochitlan, Guerrero (Mexico) - Reyna-Avila, Leticia; Peña-Marcial, Elvia; Pérez-Cabañas, Rodrigo; Lorenzo-Ángel, Luz Areli; Molina-Machuca, Diana; Aparicio-Tejeda, José Martin (Universidad y Salud, 2023)
Introduction: Depression in older adults in an important aspect since it affects significantly their health and quality of life. As people age, they may experience physical, emotional, and social changes that make them more susceptible to depression. Based on estimations from the World Health Organization, the global population over 60 years of age with some depressive symptoms will increase from 12% to 22% between 2015 and 2050. Objective: To identify the prevalence and factors associated with depression in older adults from the municipality of Mochitlan, Guerrero. Materials and methods: Mixt quantitative research with an analytical cross-sectional design and a simple random sampling of 26 older adults. Information was collected through a multiple choice survey administered by the researchers using an instrument with four sections. The ethnographic method was used for the qualitative approach, through a semi-structured interview to a focus group of seven older adults, with 3 open questions. Results: Mild (38.46%), moderate (7.69%), and serious (3.85) was found. The associated factors were: female gender; type of work; and monthly income. The qualitative analysis showed positive and negative emotions. Conclusions: 50% of the population had some type of depression.